Adapting to the digital trade era: challenges and opportunities (World Trade Organization GenevaCH, 2021)
Adapting to the digital trade era: challenges and opportunities looks at how the rapid adoption of digital technologies could help developing countries increase their participation in world trade. It also reviews the role that domestic policies and international co-operation can play in creating a more prosperous and inclusive future for these countries. This publication marks the conclusion of the second phase of the WTO Chairs Programme (WCP). It brings together contributions from the WCP Chairholders of Phases I and II, Advisory Board members, the WCP team at the WTO and other WTO Secretariat staff. The WCP is an important part of the WTO's efforts to build trade capacity and to work jointly with academic institutions in developing countries.
[2 copies]